2022
DOI: 10.1016/j.jmii.2021.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory etiological surveillance among quarantined patients with suspected lower respiratory tract infection at a medical center in southern Taiwan during COVID-19 pandemic

Abstract: Background A comprehensive study of respiratory pathogens was conducted in an area with a low prevalence of COVID-19 among the adults quarantined at a tertiary hospital. Methods From March to May 2020, 201 patients suspected lower respiratory tract infection (LRTI) were surveyed for etiologies by multiplex polymerase chain reaction (PCR: FilmArray TM Respiratory Panel) test combination with cultural method, viral antigen detection and serologic surveys. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 38 publications
1
10
0
Order By: Relevance
“…Out of the nine studies included [ 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ], most studies were retrospective [ 35 , 37 , 38 , 39 , 40 , 41 ], one article was cross-sectional [ 36 ], and two articles were prospective [ 42 , 43 ]. Regarding the place where the studies were conducted, there was a heterogeneous result since each study took place in another country, as follows: Saudi Arabia [ 35 ], Romania [ 36 ], Israel [ 37 ], Italy [ 38 ], Taiwan [ 39 ], Austria [ 40 ], France [ 41 ], Germany and Switzerland together [ 42 ], and Peru [ 43 ]. Regarding the sample size, almost half of the studies (44.4%) had a sample size of less than 100 patients [ 35 , 37 , 40 , 43 ], while the others (55.6%) ranged from 178 to 489 patients [ 38 , 39 , 41 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Out of the nine studies included [ 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ], most studies were retrospective [ 35 , 37 , 38 , 39 , 40 , 41 ], one article was cross-sectional [ 36 ], and two articles were prospective [ 42 , 43 ]. Regarding the place where the studies were conducted, there was a heterogeneous result since each study took place in another country, as follows: Saudi Arabia [ 35 ], Romania [ 36 ], Israel [ 37 ], Italy [ 38 ], Taiwan [ 39 ], Austria [ 40 ], France [ 41 ], Germany and Switzerland together [ 42 ], and Peru [ 43 ]. Regarding the sample size, almost half of the studies (44.4%) had a sample size of less than 100 patients [ 35 , 37 , 40 , 43 ], while the others (55.6%) ranged from 178 to 489 patients [ 38 , 39 , 41 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the place where the studies were conducted, there was a heterogeneous result since each study took place in another country, as follows: Saudi Arabia [ 35 ], Romania [ 36 ], Israel [ 37 ], Italy [ 38 ], Taiwan [ 39 ], Austria [ 40 ], France [ 41 ], Germany and Switzerland together [ 42 ], and Peru [ 43 ]. Regarding the sample size, almost half of the studies (44.4%) had a sample size of less than 100 patients [ 35 , 37 , 40 , 43 ], while the others (55.6%) ranged from 178 to 489 patients [ 38 , 39 , 41 , 42 ]. Reported data can be found in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…SARS-CoV-2, first detected in Wuhan city, Hubei province, has now infected over one billion people, causing over two million deaths globally [ 1 ]. Multiple studies have shown the epidemiology of viral infection during the COVID-19 pandemic [ 2 , 3 , 4 , 5 ], and coexisting respiratory pathogens among COVID-19 patients [ 6 , 7 , 8 , 9 , 10 ]. The epidemiology of respiratory pathogens in regions with high prevalence may be different from that in regions with low prevalence of COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…The epidemiology of respiratory pathogens in regions with high prevalence may be different from that in regions with low prevalence of COVID-19. Recently, Huang CP et al conducted a comprehensive study of respiratory pathogens in a Taiwanese population using multiplex PCR [ 3 ]. They showed that 59.7% of identified organisms were bacteria, and viruses accounted for 23.9%.…”
Section: Introductionmentioning
confidence: 99%